2018
DOI: 10.2147/copd.s163826
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists' training to improve inhaler technique of patients with COPD in Vietnam

Abstract: BackgroundIncorrect use of inhalers is very common and subsequently leads to poor control of COPD. Among health care providers, pharmacists are in the best position to educate patients about the correct use of inhaler devices.ObjectiveThe objective of this study was to evaluate the impact of pharmacist-led training on the improvement of inhaler technique for COPD patients in Vietnam.Patients and methodsFor this pre- and post-intervention study, standardized checklists of correct use of metered-dose inhalers (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 27 publications
3
34
2
Order By: Relevance
“…Community pharmacists are particularly situated to regularly check inhaler technique when patients drop off new inhaler prescriptions or pick up refills. Pharmacist interventions can help to improve the inhaler technique of asthma and COPD patients [14,26,27]. Furthermore, patients trust and attempt to follow the pharmacist's inhaler technique instructions [28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Community pharmacists are particularly situated to regularly check inhaler technique when patients drop off new inhaler prescriptions or pick up refills. Pharmacist interventions can help to improve the inhaler technique of asthma and COPD patients [14,26,27]. Furthermore, patients trust and attempt to follow the pharmacist's inhaler technique instructions [28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients trust and attempt to follow the pharmacist's inhaler technique instructions [28]. The patient's inhaler technique declines over time and thus, regular checks and counseling is required to ensure therapeutic stability [27]. The Global Initiative for Chronic Obstructive Lung Disease-(GOLD) and Global Initiative for Asthma (GINA) guidelines stipulate that inhaler technique needs to be assessed regularly, but do not offer a suggested time frame for re-evaluation [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that implementation of inhaler training achieves a measurable improvement in inhaler technique [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“… 41-43 Pharmacist-led interventions significantly improve inhaler technique in patients with COPD and supplement physician-based education. 15 , 44 In a large single-intervention study of patients with a diagnosis of asthma or COPD ( n = 757), inhalation technique was assessed by a CP at baseline and after 4 to 6 weeks of intervention using a 21-item checklist. Pharmacist-led training reduced the number of patients making 1 or more errors while performing inhalation technique from 597 patients (78.9%) to 214 (28.3%).…”
Section: Treatment Adherence and Correct Inhaler Usementioning
confidence: 99%